Das Bochum-Projekt : Industrielandschaft. - Frankfurter Hof, Mainz; Kunsthalle Darmstadt, Darmstadt; Jahrhunderthalle Bochum; Ahuis, Helmut; Durth, Werner; Ganser, Karl; Grebing, Helga; Klinkner, Martin; Krau, Ingrid; Lörincz, Peter; Marhenke, Dorit; Robeck, Ulrike; et al. (Darmstadt : Kunsthalle Darmstadt, 1991)
Altzweig, Daniel ; Annel, Barbara ; Birkner, Babette ; Braun, Heribert ; Durth, Werner ; Ferhat, Marie-Paule ; Flommersfeld, Stefan ; Fritsch, Kathrin ; Fuchs, Katja ; Gassen, Susann ; Gottwald, Juliane ; Guthörl, Markus ; Karch, Michaela ; Keldenich, Barbara ; Klinkner, Martin ; Knorr, Peter ; Kreiensieck, Joachim ; Lamb, Hans-Jürgen ; Lechner, Simone ; Lörincz, Peter ; Mannella, Alfonso ; Negenborn, Heike ; Poganiuch, Thomas ; Räth, Siegfried ; Robischon, Daniel ; Schwartz, Verena ; Schwarz, Renate ; Senzig, Pascale ; Sieben, Helmut ; Steinke, Irmgard ; Tepel, Jan ; Wadle, Susanne
biografie
Das Bochum-Projekt : Industrielandschaft, Bildende Kunst - Fachbereich 24 Universität Mainz in Kooperation mit der Universität Bochum, Jahrhunderthalle Bochum 1991 / Frankfurter Hof, Mainz, 1991 / Kunsthalle Darmstadt, 1992
Duits
boek